Recovery of phosphate from piggery biogas slurry by ultrasonication, aeration and addition of MgO desulfurization waste residue. (20th February 2019) - Luo, Zifeng; Peng, Junjie; Wang, Dehan; Yang, Jie
Abstract: The traditional phosphorus recovery process for piggery wastewater has not utilized the large amount of phosphorus in the biogas residue, resulting in a low phosphorus recovery percentage. This study uses an ultrasonic pretreatment step to release phosphorus from the biogas residue using magnesium oxide desulfurization waste residue (MDWR) as a low-cost magnesium source. CO2 is removed by aeration stripping to increase the pH of the system. The results showed that when the ultrasonication time was 80 min and the ultrasonic energy density was 1000 W·L −1, the phosphorus release was increased by 109.31%. Using an MDWR addition amount of 0.8 g·L −1, initial pH of 9.5, and aeration time of 2 h, the recovery percentage of PO4 3- -P was 98.90%, the best recovery effect. The analysis shows that the recovered product is mainly struvite. The ultrasonic and aeration/MDWR addition combination process is thus considered to be a promising technology. Graphical abstract: Highlights: Ultrasonic pretreatment promoted the release of phosphorus from biogas residues. The CO2 in wastewater is removed by aeration to increase the pH. The use of MgO desulfurization waste residue as Mg source is low-cost.